Expression of Procollagen A1 Type I Induced by Two Different Dentine Bonding Systems in Human Pulp Fibroblasts. (May 2013) - Orsini, G.; Mattioli-Belmonte, M.; Orciani, M.; Mazzoni, A.; Teti, G.; Falconi, M.; Putignano, A.; Breschi, L.
This study aimed to evaluate the effects of two different dentine bonding systems (DBSs) on primary cultures of human pulp fibroblasts (HPFs). Cell viability and procollagen α1 type I expression were investigated. Polymerised resin disks of the bonding agent from a two-step self-etch system and of the primer/bonding agent from a two-step etch-and-rinse system were used to condition culture medium for 24 or 96 h. HPFs were incubated in control (untreated) or DBSs-conditioned medium for 24 h. HPF viability was determined using the 3-dimethylthiazol-2, 5-diphenyltetrazolium bromide (MTT) assay. Western blot analysis was used to analyse procollagen α1 type I expression. Statistical analyses were performed using Student's t -tests. The results showed that HPFs incubated with DBSs-conditioned medium for 24 h demonstrated a significant reduction in the percentage of viable cells versus cells incubated with control medium (45% for self-etch DBS and 30% for etch-and-rinse DBS; p < 0.05), whereas this percentage increased significantly after exposure to the 96h DBSs-conditioned medium (62% and 77%, respectively; p < 0.05). Procollagen α1 type I expression in HPFs was strong for control specimens, but decreased in 24 h-DBSs-conditioned medium, and was abolished with 96 h-DBSs-conditioned medium. In conclusion, HPF exposure to medium containing eluates of the different DBSs led to an early cytotoxic effect (24 h) that decreased after a conditioning time of 96 h, whereas procollagen α1 type I expression decreased at 24 h and was absent after 96 h. Procollagen α1 type I expression may be a useful parameter for evaluating DBSs biocompatibility.